Memorandum of understanding between Universiti Teknologi MARA and Sukhotai Thammathirat Open University / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Sukhotai Thammathirat Open University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.